Veterinary Forensic Pathology, Volume 1 (Springer International Publishing, 2018)
This richly illustrated two-volume book offers a comprehensive and essential reference guide for veterinary pathologists and clinical veterinarians interested in performing animal necropsies for forensic casework. It presents a broad range of animal crime cases, with particular focus on the post mortem examination and the observed pathology. This first volume introduces readers to veterinary forensics and the role of the veterinary pathologist in animal crime investigations. It guides them through the process of evidence collection and documentation, and covers the fundamentals of forensic necropsy and the estimation of time since death. In-depth descriptions of how to conduct the forensic evaluation of various traumatic injuries, firearm injuries, and asphyxia are also provided. .